2018
DOI: 10.1016/j.jtherbio.2017.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Investigating factors affecting the body temperature of dogs competing in cross country (canicross) races in the UK

Abstract: Increasing numbers of people are running with their dogs, particularly in harness through the sport canicross. Whilst canicross races are typically held in the winter months, some human centred events are encouraging running with dogs in summer months, potentially putting dogs at risk of heat related injuries, including heatstroke. The aim of this project was to investigate the effects of ambient conditions and running speed on post-race temperature of canicross dogs in the UK, and investigate the potential ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 27 publications
3
28
2
Order By: Relevance
“…Dark‐coloured hair coat absorbs more solar radiation and stores heat than white‐coloured hair coat in cows . Further, body temperature of dogs with dark‐coloured hair coat is higher than that of those with light‐coloured hair coat after races . Our results were not consistent with these previous reports.…”
Section: Discussioncontrasting
confidence: 99%
“…Dark‐coloured hair coat absorbs more solar radiation and stores heat than white‐coloured hair coat in cows . Further, body temperature of dogs with dark‐coloured hair coat is higher than that of those with light‐coloured hair coat after races . Our results were not consistent with these previous reports.…”
Section: Discussioncontrasting
confidence: 99%
“…The techniques utilized to assess temperature, panting and water consumption are non-technical, readily available methods for canine handlers or owners to assess thermal status of dogs in the field, and thus are important to prevention of heat related injury. These data provide critical evidence to dispute the theory that dark coat color is a risk factor for thermal stress which is reported across several forums including veterinary textbooks and previously published articles [1–4]. In this experiment, dark and light-colored dogs exposed to the same environment showed a similar heat gain and loss (mean peak rectal 40.31±0.37 °C and mean peak GI temperatures 40.65±0.37 °C respectively).…”
Section: Discussionmentioning
confidence: 61%
“…Darker coat color has been suggested as a potential risk factor for heat injury in dogs in several publications [1–4] However, little evidence is available to support this theory, and a majority of these claims appear in the introduction or discussion sections of publications, or in review articles, with no supporting data. One study in Greyhounds reported higher rectal temperatures in darker colored dogs following exercise but utilized greater numbers of males in the darker coat participant group.…”
Section: Introductionmentioning
confidence: 99%
“…Another recent study did not find any direct correlation between ambient conditions and the post-race body temperature of dogs competing in canicross races. However, their results suggested that male dogs, dark coateddogs, and increased speed of running could represent a risk of heatstroke [16]. Greyhounds following even short periods of strenuous exercise commonly exhibit cramps and muscular fatigue [17].…”
Section: Discussionmentioning
confidence: 99%